Adult Graduate Students' Perceptions of Gender & Race: Implications for Program Development in Rural Communities - Catherine A. Hansman; Mary H. Jackson; Dale F. Grant; Leon E. Spencer (Adult Education Research Conference, 1999)
The purpose of this study was to assess the existing levels of awareness toward issues of race and gender in graduate students. Implications for curriculum planning are that faculty members should encourage sensitivity to diversity in all of their classes through small group discussions, case studies, presentations concerning racial and gender issues, and readings that encourage multiple views of issues.